2022
DOI: 10.1186/s13023-022-02535-y
|View full text |Cite
|
Sign up to set email alerts
|

Lung and chest wall volume during vital capacity manoeuvre in Osteogenesis Imperfecta

Abstract: Background Although Osteogenesis Imperfecta (OI) affects the connective tissue, pulmonary function might be compromised because of thoracic deformities. OI is known to be a restrictive lung disease, but spirometry provides global measurement without localizing the site of the restriction. Opto-electronic plethysmography (OEP), is a non-invasive method able to underline altered respiratory function as well as ventilatory thoraco-abdominal paradoxes during spontaneous breathing. We aimed to recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Previous studies also emphasized the importance of intramuscular fat content and distribution for muscle function [ 17 , 18 ]. Meanwhile, lower muscle density may indicate that the progressive chest deformities presented by OI patients tend to affect pulmonary function [ 25 ]. Therefore, this similarity results may suggest that muscle density measured in the trunk muscles may represent a more clinically meaningful indication of muscle performance and associate with clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also emphasized the importance of intramuscular fat content and distribution for muscle function [ 17 , 18 ]. Meanwhile, lower muscle density may indicate that the progressive chest deformities presented by OI patients tend to affect pulmonary function [ 25 ]. Therefore, this similarity results may suggest that muscle density measured in the trunk muscles may represent a more clinically meaningful indication of muscle performance and associate with clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive reduction in lung function in OI is associated with a higher risk of lung infection, potentially leading to respiratory failure and mortality. , Collagen and elastin, essential for supporting respiratory mechanics, play a crucial role in lung function, and their abnormalities in OI impact lung structure and function. It has been suggested that physicians assess lung function in OI patients during initial examinations to determine the extent of lung involvement and provide innovative treatments for lung care …”
Section: Oi Diagnosismentioning
confidence: 99%
“…It has been suggested that physicians assess lung function in OI patients during initial examinations to determine the extent of lung involvement and provide innovative treatments for lung care. 130 Some mouse models of OI have shown initial pathological changes in the lungs. 131 For instance, the Aga2 mouse model exhibited altered gene expression in both cardiac and pulmonary primary fibroblasts, potentially leading to severe cardiopulmonary issues and neonatal mortality.…”
Section: ■ Oi Diagnosismentioning
confidence: 99%